2015
DOI: 10.14310/horm.2002.1611
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the RET Cys634Tyr mutation and Gly691Ser functional polymorphism in Iranian families with multiple endocrine neoplasia type 2A

Abstract: PuRPose: Multiple endocrine neoplasia type 2A (Men2A) is a complex autosomal dominant inherited syndrome characterized by medullary thyroid carcinoma (Mtc), pheochromocytoma and primary parathyroid hyperplasia. In patients with only one or two clinical features, identification of a germ line Ret (Rearranged in transfection) mutation is required to make the diagnosis and initiate genetic counseling. MetHods: we analyzed blood dnA from three Iranian families with three generations of Men2A including 20 affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This mutation comprised 53% of all detected mutations in this study. The present study showed that mutations in exon 11, especially at codon 634, are commonly observed in the Iranian population, which is consistent with other studies [15][16][17][18][19]. Interestingly, follow-up studies in IR-F25 family showed that a 19-year-old carrier, IV-2, did not manifest any MEN2A phenotypes unlike other carriers.…”
Section: Clinical and Molecular Ndingssupporting
confidence: 93%
See 2 more Smart Citations
“…This mutation comprised 53% of all detected mutations in this study. The present study showed that mutations in exon 11, especially at codon 634, are commonly observed in the Iranian population, which is consistent with other studies [15][16][17][18][19]. Interestingly, follow-up studies in IR-F25 family showed that a 19-year-old carrier, IV-2, did not manifest any MEN2A phenotypes unlike other carriers.…”
Section: Clinical and Molecular Ndingssupporting
confidence: 93%
“…This variant was predicted to be likely benign by InterVar, benign by polyphen2, disease causing by mutation taster and tolerated with SIFT score 0.43 by SIFT web server (Table 2). [15][16][17][18][19]. It has been stated that mutations at codon 634 are the most frequent mutation in Caucasians [20].…”
Section: Clinical and Molecular Ndingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VHL variant is predicted pathogenic by SIFT and PolyPhen tool and has been reported for its association with pheochromocytoma (CM951287) when RET (rs1799939) has been reported for its association with the disease in ClinVar database. [ 6 ]…”
Section: Case Reportmentioning
confidence: 99%